Nativism or Universalism: Situating LGBT Discourse in the Philippines - Garcia, J. Neil C. (Archīum Ateneo, 2024)
Despite or precisely because of the fact that it is being increasingly globally invoked, the LGBT signifier bids us to understand its discursive performances in various localities, particularly in the global south, whose conservative traditions this form of politics most visibly challenges, at the same time that it can only do so translationally—which is to say, as a form of transcultural syncretism. More specifically, this paper offers a postcolonial reading of LGBT discourse in the Philippines, examining the confluence between the discourse of Western “psychospirituality” and the local idiom of interiority (kalooban), as evinced, in particular, in the minoritized identity of the bakla. This conceptual history concludes with the proffering of a theoretical argument about the usefulness of a moderate nativist perspective, that allows for the inclusion of hybridity in the analysis of heteronormative sexual and gendered constructions in sites outside the sexological tradition from which they originally arose.